Furfural: hemicellulose/xylosederived biochemical - Mamman, Ajit Singh; Lee, Jong-Min; Kim, Yeong-Cheol; Hwang, In Taek; Park, No-Joong; Hwang, Young Kyu; Chang, Jong-San; Hwang, Jin-Soo (Biofuels Bioproducts & Biorefining-Biofpr, 2008)
Hemicellulose, the second, most common polysaccharide in nature constitutes approximately 20-35% of lignocellulosic biomass. Effective utilization of biomass, hitherto underutilized, is gaining tremendous importance for the production of energy, fuels, and chemicals. Amongst the vast array of chemicals derived from lignocellulosics, furfural is the key chemical that finds wide applications in oil refining, plastics, pharmaceutical and agrochemical industries. There is no synthetic route for the production of furfural. A few conventional technologies currently in practice for its separation and subsequent isolation are appropriately reviewed. Major disadvantages associated with processes currently used for the production of furfural based on acid-catalyzed hydrolysis have been discussed. A need to develop a process which is devoid of all the shortcomings associated with conventional process is emphasized. Several important aspects of chemistry underlying the acid hydrolysis of xylose are discussed. The importance of myriad pre-treatment steps involved to surmount the physical and chemical barriers and to liberate xylose from the confines of acid-resistant layer of lignin has been emphasized. New developments in the production of furfural from cyclodehydration of xylose using solid acid catalysts in the recent past have been reviewed appropriately in present communication. Finally, the production of furfural and furfuryl alcohol, their domestic market and export in China deserve some coverage and therefore have appropriately been discussed as well. (c) 2008 Society of Chemical Industry and John Wiley & Sons, Ltd
Keywords: acid hydrolysis; cyclodehydration; furfural; Hemicellulose; pre-treatment of lignocellulosics; Xylose

Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts